MANAJEMEN PEMBINAAN PEMAHAMAN AGAMA ISLAM DI LEMBAGA NON KEPENDIDIKAN - Widodo, Wahyudi (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2023)
To provide an understanding of the Islamic religion to someone, religious development management is needed as all activities carried out by a person in order to provide assistance to other people who experience spiritual difficulties in their living environment with the aim that the person is able to overcome it themselves because awareness or self-surrender arises. the power of God Almighty. This article looks at the management of Islamic religious development from various backgrounds in a person's environment in non-educational institutions, using qualitative descriptive research methods based on observations in the military, police, correctional institutions and public market schools. The results and conclusions from the discussion of this article are that Islamic religious formation is carried out well in various institutions by using existing facilities and infrastructure to support religious formation activities and by using certain media and methods, for example through vocational lectures or oral recitation, istigasah, yasinan, tahlilan, and commemoration of Islamic holidays